Change of Generations in Lithuanian Photography: Changes of Sociality in Iconography - Kavaliauskas, Mindaugas (Sociologija. Mintis ir veiksmas, 2002)
From nineteen Sixties to nineties Lithuanian photography reached its highest maturity. Its acclaim in the former Soviet Union prompted the apparition of a term Lithuanian school of photography, defining the mainstream of Lithuanian photography of the time. The authors to participate in this cultural phenomenon created a considerable body of photographic works, often metaphorically depicting Lithuanian ethnic culture and rural life. During the last decades the debates on the issues of the contemporary photographic creation are rising, implying questioning, whether or not the works of the newer generation lack creative maturity, Whether they are worth of being exposed next to those made by classics. This article provides an overview of similarities and differences in the work of the Lithuanian school of photography and the generation of the independent Lithuania, using a complex method of social iconography. The usage of this method will guide the discourse from the offsprings of the socially-based national art and social photography to the overview and localization of the Lithuanian social photography in the global scene. The research aims to emphasize the basic iconological differences in the works of the two creative generations, to name the changes of the Lithuanian social and cultural habits and to detennine if the iconography of the Lithuanian photography corresponds to its period of time. Two types of social photography are distinguished - social documentation and semiotic communication. Conclusions. The iconographic formulas, practiced by the photographers (1960-1990), like old persons portraits, are common also to other Eastern European countries. The frequent festive aspect (religious holiday, manifestation, basketball team Victory etc.) works as a reason for picture-taking, and expresses a Lithuanian preference of a holiday to workday, exterior to interior, spiritual to material, anecdote to invented story. Very few signs of material culture of the Soviet period appear. Inthe works of the classics, mirror of the spiritual culture is a face of old persons. Meanwhile the young generation discovers the importance of teenagers and youth as the marginal part of the postmodern demo graphic situation. The influence of media transfers images of convicts, drunkards, disabled and other disadvantaged social groups. The crisis of the contemporary photography might lie in the lack of social descriptiveness, but not in the definition of national, social or private identities.
Keywords: iconography; iconographic model; social photography; social documentation; communication of meaning; typographic culture; visual culture